What are the believes, spiritual, subcultural, religious, traditional, and family structure of perpetrators of domestic violence? A question for further studies - Ghahari, Shahrbanoo; Imani, Saeed; Bolhari, Jafar (Social Determinants of Health, 2017)
What is believes, spiritual, subcultural, religious, traditional, and family structure of Perpetrators of domestic violence? A question for further studies